ERP System Evaluation on SOFI XP Based Accounting Module in Software House Industry - Mardallena, Shinta; Melen, Melen; Davinelya, Denen; Noerlina, Noerlina (ComTech: Computer, Mathematics and Engineering Applications, 2015)
Accounting module is an important module for a company business process. The roles are in the form of parameter calculation of profits, losses and financial performance based on transaction, which basically is a real-time reporting system. The amount of company needs on accounting indicates that the accounting is one of the resources which support the establishment of a company. Thus, the company constantly improves the accounting performance, especially in handling of receivables, debts, and cash transactions. Evaluations which were performed at SOFI XP-based ERP system aims to provide a solution to a problem that was discovered during the analysis of the system needs. This evaluation was done in two stages: by collecting data and analyzing the system that running in the company. By doing this evaluation, the documentation of system performance and the solution for problems that were found in the company can be generated.